2016
DOI: 10.1590/s1806-92902016000300004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substitution of corn for molasses in diet on growth performance, nutrient digestibility, blood characteristics, fecal noxious gas emission, and meat quality in finishing pigs

Abstract: -The objective of this experiment was to evaluate the effect of molasses as a substitute for corn in diet on growth performance, nutrient digestibility, blood characteristics, fecal noxious gas emission, and meat quality in finishing pigs. A total of 120 [(Landrace × Yorkshire) × Duroc] pigs with an average initial body weight (BW) of 54.21±2.62 kg were used in this experiment. Pigs were randomly assigned to 1 of the 3 dietary treatments on the basis of BW and sex (10 replicate pens per treatment with four pig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
3
1
3
Order By: Relevance
“…While analyzing the crude protein content, the result showed that sugarcane molasses had a low value presented at only 2.00±0.0%. is the protein content of sugarcane molasses found by this study seems to be the lowest when compared to the previous studies by Ogunwole et al (2020) and Sureshkumar et al (2016), which documented the value of crude proteins of 4.38% and 3%, respectively. According to Curtin (1983), molasses contains a low amount of nitrogen which consists of non-protein nitrogen compounds including amides, albuminoids, and amino acids.…”
Section: Proximate Composition Of Sugarcane Molassescontrasting
confidence: 76%
“…While analyzing the crude protein content, the result showed that sugarcane molasses had a low value presented at only 2.00±0.0%. is the protein content of sugarcane molasses found by this study seems to be the lowest when compared to the previous studies by Ogunwole et al (2020) and Sureshkumar et al (2016), which documented the value of crude proteins of 4.38% and 3%, respectively. According to Curtin (1983), molasses contains a low amount of nitrogen which consists of non-protein nitrogen compounds including amides, albuminoids, and amino acids.…”
Section: Proximate Composition Of Sugarcane Molassescontrasting
confidence: 76%
“…The samples were then centrifuged at 7,000 g for 5 min. The resulting serum was frozen at -20°C in microtubes (Eppendorf, Hamburg, Germany) for further blood parameter analysis (7,14) . The levels of high-density cholesterol (HDL), total cholesterol, triglycerides, urea, albumin, and gamma-glutamyl transferase (GGT) in the serum were analyzed in duplicate using a colorimetric method with commercial kits (Labtest, Lagoa Santa, MG, Brazil).…”
Section: Blood Parameter Analysismentioning
confidence: 99%
“…In addition, the difficulty of mixing limits the use of high levels of molasses in the diet (6) . A previous study showed that sugar cane molasses can be used to replace corn in the diet of finishing pigs up to 5% without affecting performance, nutrient digestibility, blood metabolites, fecal noxious gas emission, and meat quality (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, a dificuldade de mistura limita a utilização de níveis elevados de melaço na dieta (6) . Um estudo anterior mostrou que o melaço de cana-de-açúcar pode ser utilizado a´te o nível de 5% para substituir o milho na dieta de terminação de suínos sem afectar o desempenho, a digestibilidade dos nutrientes, os metabólitos do sangue, a emissão de gases nocivos fecais e a qualidade da carne (7) . Os produtos de carne suína têm sido associados a uma imagem pouco saudável devido às proporções relativas dos ácidos graxos polinsaturados e saturados (8) .…”
Section: Introductionunclassified